Environmental Migrants: A Myth? - Maystadt, Jean-François; Mueller, Valerie (International Food Policy Research Institute, 2012)
Environmental migration has been the subject of lively debate in recent years. The conundrum over why experts’ global predictions of 50 million environmental refugees were not met in 2010 best captures how messages from advocacy and research can conflict with one another (Bojanowski 2011).